The Apparent Lack of Emphasis in the Context of University Education - Thamilsellvan a/l Pamanathe; Sakinah Balqis Nor Azman; Nordini Emily Mohathir; Muhammad Ameerul Iman Shamsul Kamal; Yasin Ibrahim; Mohamad Aizi Selamat (Applied Information Technology And Computer Science, 2023)
This study investigates the challenges and opportunities in project management education within higher institutions, with a focus on key PMBOK domains. It highlights the significance of ef ective communication in project success and the need to integrate soft skills within classroom settings alongside technical knowledge in project management. It also emphasizes the significance of human resource management in education, encouraging the involvement of students in curriculum development to enhance engagement and practical application of theoretical knowledge. Quality management is seen as crucial for maintaining educational consistency and relevance, while time and scope management ensure well-targeted goals. The abstract suggests future research through a comparative analysis of dif erent educational approaches and the importance of collaborations between educational institutions and industries to provide real-world experiences to students.